Proton play in the formation of low molecular weight chitosan (LWCS) by hydrolyzing chitosan with a carbon based solid acid. (20th October 2016) - Krishnan, R.Akhil; Deshmukh, Pranjal; Agarwal, Siddharth; Purohit, Poorvi; Dhoble, Deepa; Waske, Prashant; Khandekar, Dileep; Jain, Ratnesh; Dandekar, Prajakta
Graphical abstract: Highlights: Carbon based solid acid was used to produce low molecular weight chitosan from their high molecular weight parent. Insitu IR study of the reaction confirmed the depolymerization of the chitosan. Molecular weight analysis of the products showed a more than 10 times decrease in the molecular weight of the product. The Carbon based solid acid was capable of reuse till 4 times, without regeneration of the solid acid. Green approach for hydrolysis of carbohydrate polymers like chitosan. Abstract: Low molecular weight chitosan (LWCS) constitute a special class of value added chemicals that are primarily obtained from crustacean shells, which are the main water pollutants from crabs and shrimp processing centers. Unlike chitin and chitosan, LWCS possess improved solubility in water and aqueous solutions, making them widely applicable in numerous fields ranging from drug delivery to waste water treatment. Among the methods employed for their production, chemical breakdown by strong liquid acids has yielded good success. However, this method is met with severe concerns arising from the harsh nature of liquid acids, which may corrode the reactors for commercial synthesis, and their limited reusability. The physical methods like ultrasound and microwave are energy intensive in nature, while the enzymatic methods are expensive and offers limited scope for reuse. We have attempted to overcome these problems by employing carbon based solid acid (CSA) for hydrolyzing chitosan to LWCS. CSA can be easily produced using activated carbon, a cost-effective and easily available raw material. Reactions were carried out between chitosan and CSA in a hydrothermal glass reactor and the products, separated by cold centrifugation, were purified and dried. The dried products were characterized for their molecular weight and solubility. Results indicated more than ten-fold decrease in the molecular weight of chitosan and the product exhibited water solubility. The CSA could be used upto four times, without regeneration, to give a consistent quality product. The aqueous solution of resulting LWCS exhibited a pH of 6.03 ± 0.11, as against the acidic pH range of solutions of commercially available LWCS, indicating its suitability for biomedical applications. Our investigation facilitates a 'green approach' that may be employed for commercial production of value added chemicals from waste products of marine industry.